ARAHAN PENGEMBANGAN INDUSTRI PARIWISATA BAHARI PADA DAERAH 3 T (TERDEPAN, TERPENCIL DAN TERBELAKANG) (Studi Kasus di Kawasan Kepulauan Tiworo Kabupaten Muna Barat) - Handa, Muhammad Idham (EDUTECH CONSULTANT, 2019)
This study uses a qualitative approach and survey design and field observations. Samples (informants) were determined by purposive sampling. The results showed that the potential and main tourist attraction objects of the Tiworo Islands are the existence of small islands (13 islands) and the waters of the Tiworo Strait which are rich in diversity of marine life where the potential is categorized according to marine tourism. The effective carrying capacity (ECC) of tourism in the Tiworo Islands is 93,131 people per day or 11,641 people in every 3 hours without causing disturbance to the ecosystem, this means that the development of the tourism industry is very potential given the average number of tourist visits in Muna Barat around the year 018 as many as 1,749 people or 60 people / day. Availability of facilities both basic, functional and supporting facilities in the Tiworo Islands is currently quite adequate in serving tourists. The direction of the development of the marine tourism industry in remote and backward areas in the Tiworo Islands is carried out through two approaches namely; (1) Direction of tourism industry development according to location and spatial structure by dividing four hierarchies according to the tourism function zone (2) Direction of tourism industry development according to the carrying capacity of eco-green-based regions.